Transitividade e movimento em relatividade de de Sitter - Sampson Sandia, Almeira del Carmen [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
There are currently an agreement that special relativity, whose kinematic is ruled by the Poincaré group, fails near the Planck scale. As a consequence, new kinematics have been proposed. An alternative to those theories is the de Sitter special relativity, which assumes a violation, not of the Lorentz symmetry, but of the translation symmetry. In this theory the cosmological constant appears as a kinematic effect and not as an exotic element ?lling the Universe. Taking into account the appropriate transitivity properties, a new conserved current and a new family of maximizing trajectories are obtained. These trajectories introduce a new notion of motion, given by a combination of translations and proper conformal transformations

Existe atualmente um consenso de que a relatividade especial, cuja cinemática é governada pelo grupo de Poincaré, deixa de ser válida próxima à escala de Planck. Como consequência, novas cinemáticas têm sido propostas. Uma alternativa a essas teorias é a relatividade especial de de Sitter, a qual pressupõe uma violação, não da simetria de Lorentz, mas da simetria de translação. Essa teoria inclui a constante cosmológica como um efeito cinemático e não como um elemento exótico que permeia o Universo. Considerando as propriedades de transitividade do espaçotempo de Sitter, são obtidas uma nova corrente conservada e uma nova família de trajetórias. Essas trajetórias introduzem uma nova noção de movimento, dado por uma combinação de translações e transformações conformes próprias
Keywords: Gravitação; Cosmologia; Relatividade especial (Fisica); Espaço e tempo